Study of career development in children from a developmental-contextual perspective - Araújo, Alexandra Maria Dantas de Castro (2009)
Career development is a longitudinal process, from childhood to adulthood, which is influenced by personal and contextual factors. Vocational literature has described childhood as a formative period, as the bases of exploration and vocational interests, values, attitudes and skills are established in the first years of life. This study starts with an overview of the major theoretical approaches and research trends in the study of children’s careers. A particular focus on the developmental-contextual approach is adopted, as an integrative framework to capture the complexity of processes and results that occur in the first years of life in that domain. The application of such a perspective to the study of the evolution of children’s vocational behaviour leads to a discussion of the nature of change in the first years of life, of the child as a shaper of development and context, and of the impact of contexts on children’s. Finally, we present implications of the adoption of the referred contextual approach for future research.